Principlism and Personalism. Comparing Two Ethical Models Applied Clinically in Neonates Undergoing Extracorporeal Membrane Oxygenation Support - Di Nardo, Matteo; Dalle Ore, Anna; Testa, Giuseppina; Annich, Gail; Piervincenzi, Edoardo; Zampini, Giorgio; Bottari, Gabriella; Cecchetti, Corrado; Amodeo, Antonio; Lorusso, Roberto; Del Sorbo, Lorenzo; Kirsch, Roxanne (Frontiers in Pediatrics, 2019)
Extracorporeal membrane oxygenation (ECMO) is a technology used to temporarily assist critically ill patients with acute and reversible life-threatening cardiac and/or respiratory failure. This technology can often be lifesaving but is also associated with several complications that may contribute to reduced survival. Currently, neonates supported with ECMO are complex and bear an increased risk of mortality. This means that clinicians must be particularly prepared not only to deal with complex clinical scenarios, but also ethical issues associated with ECMO. In particular, clinicians should be trained to handle unsuccessful ECMO runs with attention to high quality end of life care. Within this manuscript we will compare and contrast the application of two ethical frameworks, used in the authors’ institutions (Toronto and Rome). This is intended to enhance a broader understanding of cultural differences in applied ethics which is useful to the clinician in an increasingly multicultural and diverse patient mix.